2022
DOI: 10.1161/circinterventions.122.012182
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Intracoronary Imaging Optimization in Contemporary Percutaneous Coronary Intervention: A Report From the BMC2 Registry

Abstract: Background: Intracoronary imaging (ICI) during percutaneous coronary intervention (PCI) improves outcomes, yet hospital- and physician-level variabilities in ICI and its impact on ICI use in contemporary PCI remain unknown. This study was performed to evaluate hospital- and physician-level use of ICI to optimize PCI. Methods: Using data from a large statewide registry, patients undergoing PCI between July 2019 and March 2021 were studied. The primary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…A nationwide US study showed that use of intravascular imaging was below 5% between 2004 and 2014 45. A large state registry in Michigan showed that only 5.6% of all percutaneous coronary interventions in Medicare patients were done with intravascular ultrasonography 46. The results of this meta-analysis should encourage wider adoption of intravascular imaging guided percutaneous coronary intervention in clinical practice.…”
Section: Discussionmentioning
confidence: 89%
“…A nationwide US study showed that use of intravascular imaging was below 5% between 2004 and 2014 45. A large state registry in Michigan showed that only 5.6% of all percutaneous coronary interventions in Medicare patients were done with intravascular ultrasonography 46. The results of this meta-analysis should encourage wider adoption of intravascular imaging guided percutaneous coronary intervention in clinical practice.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study noted that operator variability was an even stronger predictor for IVI use than any patient or procedural characteristic. 3 To our knowledge, this is the first study associating specific physician characteristics with IVI use.…”
Section: Discussionmentioning
confidence: 90%
“…Despite randomized trials 1 showing reduced target vessel failure and major adverse cardiovascular events with intravascular imaging (IVI) guided percutaneous coronary intervention (PCI), IVI is used in only 7.8% of all PCI in the United States. 2 , 3 Operator variation in IVI use and characteristics of operators with low IVI use have not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…Although use of intravascular imaging in the United States between 2004 and 2017 was 5% to 6%, it has since increased. 10 At 48 hospitals participating in the State of Michigan the Blue Cross Blue Shield of Michigan Cardiovascular Consortium, the use of intravascular imaging for PCI guidance increased from 7.2% to 22.6% between July 2019 and March 2021. The authors speculate that reasons underlying this increase are more evidence of clinical benefits of intravascular imaging, and an emphasis on quality at the quarterly registry meetings.…”
Section: Potential Obstacles To Widespread Implementation Of Intravas...mentioning
confidence: 99%